Passiflora incarnata L., herba, in benzodiazepine tapering: long-term safety and efficacy in a real-world setting - Carminati, Matteo; Tondello, Mattia; Zanardi, Raffaella (Frontiers in Psychiatry, 2024)
Aim of the present study was to confirm the possible role of P. incarnata L., herba as an add-on treatment for BDZ tapering, and its efficacy in maintaining BDZ discontinuation over time. We confirmed this effect to be sustained over time, and P. incarnata showed to be easily discontinued with no rebound, withdrawal or psychological dependence effect. Moreover, we investigated possible risk factors for a poor outcome of BDZ tapering, highlighting a possible role of personality disorders as the most relevant clinical factors associated with a not complete BDZ discontinuation.